Occult hypoperfusion is associated with increased mortality in hemodynamically stable, high-risk, surgical patients - Meregalli, André (BioMed Central, 2004)
BACKGROUND: Our aim was to examine whether serial blood lactate levels could be used as predictors of outcome. METHODS: We prospectively studied 44 high-risk, hemodynamically stable, surgical patients. Blood lactate values, mean arterial pressure, heart rate and urine output were obtained at patient admission to the study, at 12, 24 and 48 hours. RESULTS: The nonsurvivors (n = 7) had similar blood lactate levels initially (3.1 ± 2.3 mmol/l versus 2.2 ± 1.0 mmol/l, P = not significant [NS]), but had higher levels after 12 hours (2.9 ± 1.7 mmol/l versus 1.6 ± 0.9 mmol/l, P = 0.012), after 24 hours (2.1 ± 0.6 mmol/l versus 1.5 ± 0.7 mmol/l, P = NS) and after 48 hours (2.7 ± 1.8 mmol/l versus 1.9 ± 1.4 mmol/l, P = NS) as compared with the survivors (n = 37). Arterial bicarbonate concentrations increased significantly in survivors and were higher than in nonsurvivors after 24 hours (22.9 ± 5.2 mEq/l versus 16.7 ± 3.9 mEq/l, P = 0.01) and after 48 hours (23.1 ± 4.1 mEq/l versus 17.6 ± 7.1 mEq/l, P = NS). The PaO(2)/FiO(2 )ratio was higher in survivors initially (334 ± 121 mmHg versus 241 ± 133 mmHg, P = 0.03) and remained elevated for 48 hours. There were no significant differences in mean arterial pressure, heart rate, and arterial blood oxygenation at any time between survivors and nonsurvivors. The intensive care unit stay (40 ± 42 hours versus 142 ± 143 hours, P < 0.001) and the hospital stay (12 ± 11 days versus 24 ± 17 days, P = 0.022) were longer for nonsurvivors than for survivors. The Simplified Acute Physiology Score II score was higher for nonsurvivors than for survivors (34 ± 9 versus 25 ± 14, P = NS). The urine output was slightly lower in the nonsurvivor group (P = NS). The areas under the receiving operating characteristic curves were larger for initial values of Simplified Acute Physiology Score II and blood lactate for predicting death. CONCLUSION: Elevated blood lactate levels are associated with a higher mortality rate and postoperative complications in hemodynamically stable surgical patients.